Pengaruh Model Pembelajaran TGT (Team Game Tournament) terhadap Aktivitas Pembelajaran Peserta didik di Sekolah Dasar - Andre Frayoga (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to analyze the influence of the Team Games Tournament (TGT) learning model on students' learning activities in elementary schools. The method used in this research is Systematic Literature Review (SLR). This research is a generalization of Classroom Action Research (PTK) and experiments that have been carried out previously. Based on the results of the article analysis, it can be concluded that the TGT (Team Game Tournament) learning model has an influence on students' learning activities in elementary schools, such as increasing students' cooperation and activeness. This is because in this model students are required to interact with each other, collaborate and discuss to achieve common goals. These various activities will motivate students to participate actively in groups. As well as deepening understanding of the material, by working together in groups students can deepen their understanding of the learning material.